INFLUENCIA DE LA FEDRA DE SÉNECA EN LA FEDRA DE UNAMUNO - Sánchez-Lafuente Andrés, Ángela; Beltrán Noguer, María Teresa (Myrtia, 1997)
The myth of Fedra, treated in the Spanish Drama by Unamuno is a recreation of the Tragedy Hipolito by Euripides, but also, and above all, the Senecan Tragedy Fedra. The Senecan Stoicism marks are present as well as the conception of human life, either Drama or Comedy. The metaphor of the "Theatrum Mundi" comes from this latin author in the Spanish Literature.